OPTIMIZATION OF OUTPATIENT TREATMENT OF BRONCHIAL ASTHMA IN SCHOOL-AGE CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Bronchial asthma is a chronic inflammatory disease of the airways, accompanied by episodes of shortness of breath, coughing, and wheezing. In school-age children, asthma is relatively common and significantly affects their physical and emotional well-being, academic performance, and overall quality of life. Therefore, modern outpatient treatment methods aimed at long-term symptom control and prevention of exacerbations are of great importance.